Groundwater Pollution Vulnerability in Kabul, Afghanistan, Assessed Using a Geographical Information System (GIS)-Based DRASTIC Model - Hasibullah Jahish; Mohammad Haroon Sarwary; Zabihullah Rasoli; Abdulhai Kaiwaan; Mohammad Aref Naimzad; Abdoullah Namdar; Sayed Javid Azimi (Revista Eídos)
Groundwater in Kabul, Afghanistan, is increasingly vulnerable to pollution due to human activities and inadequate wastewater and waste management. This study assessed groundwater vulnerability using the Geographical Information System (GIS)-based DRASTIC model, which integrates seven hydrogeological parameters: water table depth(D), recharge rate(R), Aquifer media (A), Soil media (S), topography(T), vadose zone impact(I), and hydraulic conductivity(C) in 2024. The DRASTIC Vulnerability Index (DVI) was calculated for 88 sites, with values ranging from 58 to 181, classifying the area into five zones: very low, low, medium, high, and very high vulnerability. The results showed that 33.71 % of the study area fell into the very high vulnerability category, highlighting the risk of serious pollution, especially near the Kabul River basin and septic well areas.Validation using nitrate (NO3) levels showed a strong positive correlation (R² = 0.92) with the DRASTIC model, confirming its reliability.The study highlights the urgency of implementing targeted groundwater protection policies and sustainable management strategies. By combining geographical information system tools and vulnerability modeling, this study provides valuable information to combat groundwater pollution and conserve important water resources in a rapidly urbanizing region.